2021 29th European Signal Processing Conference (EUSIPCO) 2021
DOI: 10.23919/eusipco54536.2021.9616334
|View full text |Cite
|
Sign up to set email alerts
|

Near field Acoustic Holography on arbitrary shapes using Convolutional Neural Network

Abstract: Near-field Acoustic Holography (NAH) is a wellknown problem aimed at estimating the vibrational velocity field of a structure by means of acoustic measurements. In this paper, we propose a NAH technique based on Convolutional Neural Network (CNN). The devised CNN predicts the vibrational field on the surface of arbitrary shaped plates (violin plates) with orthotropic material properties from a limited number of measurements. In particular, the architecture, named super resolution CNN (SRCNN), is able to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…displacement at a point, stiffness of the resulting geometry). We have not studied the prediction of the spatial behavior of the modes, but research in our own group has shown that this can be predicted with convolutional and autoencoders networks [13]. The path towards optimization of sound seems finally within reach, more than 300 years after Stradivari built the instruments that inspired this study.…”
Section: Discussionmentioning
confidence: 99%
“…displacement at a point, stiffness of the resulting geometry). We have not studied the prediction of the spatial behavior of the modes, but research in our own group has shown that this can be predicted with convolutional and autoencoders networks [13]. The path towards optimization of sound seems finally within reach, more than 300 years after Stradivari built the instruments that inspired this study.…”
Section: Discussionmentioning
confidence: 99%
“…We are certain that this method can be easily applied to other domains of FEM simulation and maybe used to speed up the computation with simple geometries in current FEM solvers. Furthermore, recent experiments in learning the modal response of plates seem to indicate that this approach could also be used to predict the acoustic directional response of the modes as well as their frequency 18 . A number of luthier-specific conclusions can be drawn from study.…”
Section: Discussionmentioning
confidence: 99%
“…Machine intelligence has been successfully applied to physical systems of all sorts 10 , including spin phase transitions [11][12][13] ; quantum topological transitions 14 ; and even physical problems as simple as the pendulum 15 . In computational acoustics, NN's have been employed in a wide range of tasks 16 , including the localisation of acoustic sources 17 ; nearfield holography 18 ; and acoustic scene classification 19 . To the best of our knowledge, however, AI has not yet been applied to the problem of eigenfrequencies of plates, let alone the prediction of the acoustic behaviour of violin tops.…”
Section: Introductionmentioning
confidence: 99%
“…A third category comprising deep learning emerged as an alternative approach for sound field reconstruction and a wide range of problems in the field of acoustics [23][24][25][26][27]. In [28], a convolutional neural network (CNN) has been proposed for the reconstruction of room transfer functions.…”
Section: Introductionmentioning
confidence: 99%